2021
DOI: 10.20377/jfr-426
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty in fertility intentions from a life course perspective: Which life course markers matter?

Abstract: Objective: The aim of this study is to extend our knowledge about uncertainty in fertility intentions from a life course perspective. We want to find out if life course markers such as economic circumstances, relationship status, family size, and the so-called “biological clock” (getting older) influence uncertainty in fertility intentions. Uncertainty in fertility intentions is the state in which individuals are not sure whether they will have (more) children. Background: Determining what drives uncerta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 34 publications
(56 reference statements)
2
22
0
Order By: Relevance
“…Additionally, the surveying of fertility intentions employed in this study also prevents the possibility of examining "uncertainty" in the responses. Nevertheless, the complex nature of contemporary fertility decisions involves a much higher degree of ambivalence than in the past (Rotkirch, 2021), the large share of which changes across an individual's life course (Kuhnt et al, 2020).…”
Section: Figmentioning
confidence: 99%
“…Additionally, the surveying of fertility intentions employed in this study also prevents the possibility of examining "uncertainty" in the responses. Nevertheless, the complex nature of contemporary fertility decisions involves a much higher degree of ambivalence than in the past (Rotkirch, 2021), the large share of which changes across an individual's life course (Kuhnt et al, 2020).…”
Section: Figmentioning
confidence: 99%
“…Second, the economic uncertainty is "a game-changer for European fertility dynamics" (Vignoli et al 2020, p. 4). Numerous studies have shown that risk of unemployment and an unstable financial situation negatively affect people's fertility intentions as well as their realisation (Fahlén & Oláh, 2015Kuhnt et al, 2020;Pailhé & Solaz, 2012;Schmitt, 2012). And fertility tends to decrease when economic conditions are less certain (Sobotka et al, 2011).…”
Section: Fertility Choices In the Pre-pandemic Eramentioning
confidence: 99%
“…Parental investment was indicated by contact frequency, emotional closeness, financial support and childcare help, which have been commonly used variables also in prior studies on parental investment (Rotkirch, 2018). We indicated fertility intentions by a measure demonstrating participant's intentions to have a/another child during the following 2 years; this indicator has been used also in several recent studies considering childbearing plans of younger and middle-age adults (Kuhnt et al, 2021;Wagner et al, 2019;Vidal et al, 2017). Four different parent-adult child dyads that accounted for the sex of the parents and their adult children were detected.…”
Section: Discussionmentioning
confidence: 99%
“…Our dependent variable indicated respondent's fertility intentions (see, e.g., Kuhnt et al, 2021;Wagner et al, 2019;Vidal et al, 2017 who have also studied fertility intentions with pairfam data). In the pairfam questionnaires, respondents were asked the following: "Do you intend to become a mother or father (again) over the next 2 years?."…”
Section: Methodsmentioning
confidence: 99%